CHANGING PARADIGM OF ENTEROCOCCAL INFECTIONS - MAANASA M BHASKAR; HARISH B. N (International Journal of Pharma and Bio Sciences, 2015)
Enterococci are increasingly recognized as an important nosocomial pathogen. The present study was done to establish the changing paradigm of blood culture enterococcal isolates and emergence of Enterococcus faecium as a nosocomial pathogen. A total of 150 Enterococcal isolates were obtained during the study period from January 2013 to March 2014. 68.3% and 31.7% of adult and 53% and 43% of paediatric blood culture enterococcal isolates were Enterococcus faecalis and Enterococcus faecium respectively. Antimicrobial susceptibility testing by Kirby Bauer disc diffusion revealed vancomycin resistance of 7.2% and 1.8% for adult 15.3% and 26 % among the paediatric E. faecalis and E. faecium isolates respectively. The present study demonstrates the changing spectrum of enterococcal species causing bacteremia and increasing prevalence of vancomycin resistance among E. faecium isolates. This emphasises the need for speciation of various enterococcal isolates and knowledge of antimicrobial resistance profile is necessary for management of serious enterococcal infections.